2012
DOI: 10.1038/cddis.2012.142
|View full text |Cite
|
Sign up to set email alerts
|

The retinoblastoma protein (Rb) as an anti-apoptotic factor: expression of Rb is required for the anti-apoptotic function of BAG-1 protein in colorectal tumour cells

Abstract: Although the retinoblastoma-susceptibility gene RB1 is inactivated in a wide range of human tumours, in colorectal cancer, the retinoblastoma protein (Rb) function is often preserved and the RB locus even amplified. Importantly, we have previously shown that Rb interacts with the anti-apoptotic Bcl-2 associated athanogene 1 (BAG-1) protein, which is highly expressed in colorectal carcinogenesis. Here we show for the first time that Rb expression is critical for BAG-1 anti-apoptotic activity in colorectal tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…RB has been shown be function as an anti-apoptotic factor(28) and microarray analysis demonstrated that induction of pro-apoptotic transcripts in the setting of RB depletion (Supplemental Figure 2). Many of the altered gene transcripts are pro-apoptotic genes regulated via NFκB including DR4, TRAIL, RIP1 Fas, FasL, MYC, NOTCH2 and PLK3(29).…”
Section: Resultsmentioning
confidence: 99%
“…RB has been shown be function as an anti-apoptotic factor(28) and microarray analysis demonstrated that induction of pro-apoptotic transcripts in the setting of RB depletion (Supplemental Figure 2). Many of the altered gene transcripts are pro-apoptotic genes regulated via NFκB including DR4, TRAIL, RIP1 Fas, FasL, MYC, NOTCH2 and PLK3(29).…”
Section: Resultsmentioning
confidence: 99%
“…pRB hyperphosphorylation by cyclin/CDK complexes (mainly cyclin D and CDK 4/6) is a key event for the G1 to S phase transition [19], [20]. Previous studies from our research group and others [21], [22], [23], [24] have demonstrated that pRb has an anti-apoptotic effect in specific conditions: expression of a non-cleavable form of pRb prevented cell death induced by TNF-R1 activation in cultured fibroblasts and by lipopolysaccharide (LPS) and TNF-α exposure in gastrointestinal mucosa of mice [21], [22]. Seventy percent of all tumor types have changes in the pRB pathway, with the nature of the change varying across types [14], [25], [26].…”
Section: Introductionmentioning
confidence: 80%
“…Rb is typically not mutated in colorectal cancer cells [66]. However, during cell cycle G1/S transition Rb is phosphorylated and inactivated [63,64]; thus, it is possible that it is during this time that Wnt hyperactivation by histone deacetylase inhibitors induces colorectal cancer cell apoptosis.…”
Section: Rb Wnt Hyperactivation and Apoptosismentioning
confidence: 99%